Narrative Coherence between Soundtracks and Their Series In Layangan Putus, Queen of Tears, and Doctor Foster - Nabila, Citra; Azzahra, Nur Aulia; Nurjanah, Siti (LPPM STKIP PGRI Bandar Lampung, 2024)
This study aims to analyze the narrative coherence between the soundtrack and the film series of Layangan Putus, Queen of Tears, and Doctor Foster. Using the theory of narrative coherence proposed by West and Turner (2010), this research explores three main elements: structural, material, and characterological coherence. The soundtracks in all three series play an important role in reinforcing emotional and narrative themes. Structural coherence is seen in how the soundtrack marks emotional transitions and plot developments, such as the change from quiet moments to conflict and climax. Material coherence is reflected in the harmony between the main themes of the story and the emotional atmosphere established by the soundtrack. Characterological coherence is seen from the consistency in the soundtrack that reflects the emotional portrayal of the main character. The soundtrack in the film not only supports the storyline, but also reinforces the character development and emotional atmosphere in the story, making it an essential element in building a deep narrative.